Nowy Dionizos czy syn Posejdona? De(kon)strukcja obrazu Demetriusza Poliorketesa w świetle nowożytnej historiografii - Zieliński, Tomasz (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
This article is focused on the research of modern historians concerning the importance of Dionysus and Poseidon in Demetrius Poliorcetes’ self-representation. It draws attention to the change of approach adoptedby recent studies and the multiple ambiguous interpretations that have been offered.